Livestock Farmers’ Perception on Animal Husbandry Services Rendered Under Corporate Social Responsibility (CSR) - Verma, Adesh Kumar; Chander, Mahesh; Kumar, Sanjay; Verma, MR; Kannadhasan, MS (Indian Journal of Veterinary Sciences and Biotechnology, 2020)
The Animal Husbandry sector receives only 12 percent of the total public expenditure on agriculture and allied areas resulting in underperformance of the sector. However, companies are offering different animal husbandry services under their corporate social responsibility (CSR) programs abiding Section 135(1) of Companies Act 2013. The present study was carried out to assess the perception of livestock farmers on the availability and effectiveness of animal husbandry services rendered under CSR activities. A total of 120 livestock farmers, each with a minimum one adult dairy animal was selected from the villages adopted by the selected companies for delivering CSR activities. Data were collected using a well-structured and pre-tested interview schedule through personal interviews with the respondents and analyzed appropriately to reveal the perception of livestock farmers about the availability and effectiveness of different CSR services. Most of the respondents perceived that extension, production, healthcare, and marketing services were occasionally available with average effectiveness due to the efficiency of services offered through CSR activities. Further, they perceived that the rarely available credit service had poor effectiveness. Healthcare service was the most preferred service in terms of availability and effectiveness, while credit service was the least preferred both in terms of availability and effectiveness.